A simulation study of pearlite-to-austenite transformation kinetics in rapidly heated hot-rolled low carbon steel. (5th October 2016) - Sharma, Sandeep; Nanda, Tarun; Adhikary, Manashi; T., Venugopalan; B., Ravi Kumar
Abstract: The main aim of the present research was to obtain an optimized microstructure with adequate mechanical properties in a low carbon steel. The effect of microstructure on kinetics of austenite transformation was simulated. A 3.2 mm hot rolled steel was subjected to continuous annealing to obtain properties of Dual Phase 590 grade. Kinetics of austenite transformation was studied with respect to the condition of just pearlite dissolution to form austenite under rapid heating. Annealing parameters were based on process conditions of dual phase steel production in a continuous annealing line. DICTRA was used to simulate heating rates of the order 10–500 °C/s with peak temperatures in the range 750–850 °C to predict isothermal annealing time required for complete dissolution of pearlite into austenite under different temperature-heating rate conditions. Simulation results showed dependency of temperature and heating rate on austenite transformation time. Interestingly, no significant effect of heating rate on complete pearlite dissolution into austenite was evident. Results were validated with limited experimentation on Gleeble. Microstructure analysis validated the simulation results to be accurate. The observations have pertinent inputs while designing industrial continuous annealing line parameters where rapid heating rates are generally encountered (10–20 °C/s). Graphical abstract: Highlights: Simulations to study effect of microstructure on kinetics of austenite formation Commercial software (DICTRA) used to simulate heating rates in the range 10–500 °C Simulations established the effect of heating rate, annealing temperature, and holding time. Useful for designing continuous annealing line parameters with rapid heating rates Simulation results were validated with limited experimentation on Gleeble.